Prevalence And Variation Of Club Foot In Newborns In KPK (Journal of Pharmaceutical Negative Results, 2021)
Background: Club foot, also known as congenital talipes equinovarus (CTEV), is a congenital deformity that affects the foot's musculoskeletal system. It involves twisting the foot inwards, which places a significant amount of stress on those who are impacted. Most of these disorders need immediate intervention to prevent resulting problems. Knowledge of the prevalence and distribution in different areas of KPK may be helpful when establishing and implementing the treatment plan for this disorder.Objectives: Assess the magnitude of club foot among newborns in KPK, explore the variations in club foot occurrences, and establish possible risk factors for club foot.Study Design: A descriptive cross-sectional study.Place and Duration of Study: Department of Anatomy with the collaboration of orthopedic department Nowshera Medical College from 05 April 2022 to Sept 2023Methods: The current study is a descriptive cross-sectional study that took place in the Department of Anatomy, NMC Nowshera. The study sample involved 100 newborns diagnosed with clubfoot. Records of the patients were reviewed to obtain data on the patient’s age at surgery, sex, degree of deformity, family history of deformities, and other possible risk factors like maternal health at the time of delivery, birth weight, and gestational age. Data analysis was done using statistical software to compute the prevalence and pattern or variation analysis. Results: Among the 1000 newborns screened, one hundred were found to have clubfoot, making the condition's prevalence 10%. Of the newborns affected, 60 percent were male, and 40 percent were female. The condition was categorized into 30% mild, 50% moderate, and 20% severe. Of the total instances, 70% were bilateral and 30% were unilateral. 25% of the participants admitted to having a family history of club foot, whereas 10% of mothers suffered gestational oligohydramnios and 5% experienced maternal hypertension during pregnancy, both of which affected the prevalence of this illness. Conclusion: The analysis shows that club foot is highly prevalent in KPK, with differences in the severity and manifestation of the deformity. The key to the prevention and treatment of the disease is the timely diagnosis and subsequent appropriate intervention. To avoid the disease, increased access to and refinement of prenatal care, along with more studies done on genetic and environmental risk factors, are suggested.